Study on awareness and utilization of Ayushman Bharat Arogya Karnataka scheme in Chamarajanagar taluk: a cross-sectional study - Girish B.; Jithin Surendran; Vishma B. K.; Jyothika V.; Shifa Tahreem (International Journal of Research in Medical Sciences, 2023)
Background: Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY) is India’s government-funded health insurance scheme that covers over 10.74 crore poor and vulnerable families. Karnataka has been at the forefront of successfully implementing this health scheme which named as Ayushman Bharat Arogya Karnataka (ABArK) through Suvarna Arogya Suraksha trust (SAST). Methods: This cross-sectional study was conducted in Chamarajanagar Taluk. All the 22 rural and urban field practice area of Chamarajanagara medical college and hospital were enlisted and the study subjects were randomly selected. After obtaining consent, the head of the family or in his absence the eldest adult in the households were taken as respondents. Results: The study included 1027 households; out of which 452 (44%) are card holders. The majority of ABArK card holders 434 (96%) are BPL card holders and rural residents (60%). The totals of 666 (65%) study subjects are aware about the scheme, out of which 68% are the beneficiaries. Unfortunately, only 3% of the card holders were utilized the scheme and get benefitted. Conclusions: The ABArK scheme and service utilisation by the study population were inadequate. The lack of adequate awareness and poor communication between health workers are the major factors for under-utilization of the scheme.